A cross-platform study of human situational awareness for heterogeneous low altitude autonomy - Wang, Ziyue; Xing, Yang; Zolotas, Argyrios; Perrusquía, Adolfo; Guo, Weisi; Tsourdos, Antonios (Institute of Electrical and Electronics Engineers (IEEE), 2025)
Human–autonomy teaming in the Low Altitude Economy (LAE) requires operators to manage both ground and aerial autonomous agents under time pressure, spatial uncertainty, and cognitive load. This study investigates how visual and haptic feedback affect operator situational awareness (SA) in simulated collision avoidance tasks involving cars and drones. A high-fidelity virtual environment was built using Unreal Engine 4 and AirSim, with haptic cues delivered through a wearable bHaptics vest. Twenty-two participants performed within-subject trials across visual-only and visual–haptic conditions. Results showed that haptic feedback significantly enhanced SA, particularly in dimensions related to information acquisition and spare mental capacity. Improvements were more consistent in car-based tasks, while drone scenarios exhibited greater inter-individual variability. These findings demonstrate the potential of multimodal interfaces to support cognitive performance and reduce platform-related disparities in operator SA. This work provides empirical evidence for designing adaptive, perception-aware interfaces in safety-critical human–autonomy teaming systems.
Keywords: 46 Information and Computing Sciences; 4608 Human-Centred Computing; Clinical Research